Interactive and personalized digital communication: Key predictors of political participation intention in young Moroccans - Hind Sbai; Souad Al Bakali; Hassan Azouaoui; Abdessamad Dibi (Innovative Marketing)
Through a quantitative lens, this study examines the effect of interactivity and personalization in digital communication on young individuals’ political participation intentions within a non-Western context, specifically among Moroccan youth. Furthermore, it evaluates the mediating roles of attitude and perceived behavioral control. Adopting a positivist epistemological stance, the study utilized an online survey disseminated via social media. Data were collected during a post-election period in Morocco, a time marked by significant political engagement on social media. Subsequently, a purposive sample of 423 respondents was analyzed using Partial Least Squares regression. The findings reveal a positive and significant effect of both interactivity (p < 0.01; β = 0.363) and personalization (p < 0.01; β = 0.333) on young Moroccans’ political attitudes. However, interactivity exhibited the largest effect. While personalization had a positive effect, only professionally-oriented communications resonated, challenging broader notions of personalization’s universal positive effect on political attitudes. Additionally, perceived behavioral control was positively affected mainly by personalization (p < 0.01; β = 0.200), yet its variance was minimally explained (R² = 0.092) by digital communication features alone, suggesting that other political determinants are at play. Furthermore, both political attitude and perceived behavioral control significantly predicted political participation intentions, with perceived behavioral control demonstrating a stronger effect. Finally, mediation analysis confirmed that personalized interactive communication indirectly stimulates political participation intention through both attitude and perceived behavioral control (p < 0.05). These results extend existing models, highlighting the critical role of interactivity and personalization in shaping youth political participation intention in the Moroccan context.